Nilai Moral pada Naskah Drama "Tempat Istirahat Karya" David Campton - Amanda, Irma (Jurnal Konsepsi, 2024)
This research aims to describe the results of the analysis of Moral Values contained in the drama script “Tempat Istirahat” by David Campton. The research method used is a qualitative research method with descriptive analysis, namely describing the research results in words. The theory used in this research is Thomas Lickona's theory in his book Mendidik untuk Membentuk Karakter, which divides moral values into two parts, namely universal moral values and non-universal moral values. From the results of this research, there are 9 data which are a form of moral values based on Thomas Lickona's theory.